Kontroversi Wali Mujbir dalam Kasus Pernikahan Dini di Indonesia - Mutakin, Ali; Isroiliyah (Sharia Journal and Education Center Publishing, 2024)
Abstract This article discusses the controversy surrounding the role of wali mujbir in cases of early marriage in Indonesia. Wali mujbir, as a guardian who has the authority to marry off girls without their consent, has become a topic of debate that links Islamic law with human rights, particularly children's rights. Despite having a strong foundation in classical fiqh texts, the application of wali mujbir in the modern era, especially in Indonesia, often comes into conflict with national laws that set marriage age limits. This article highlights how wali mujbir is often used to legitimize early marriage, especially in rural areas driven by social and economic factors, despite the negative impact this practice has on girls' physical, mental and social health. This research uses a qualitative method with a literature approach to analyze data from Islamic legal literature, academic studies, and reports related to the impact of early marriage. The findings show that the practice of wali mujbir in early marriage often leads to problems, including decreased access to education, increased risk of domestic violence, and reproductive health issues. In conclusion, although wali mujbir has a basis in Islamic law, its practice in the context of early marriage should be evaluated and adjusted to the principles of justice and protection of girls' rights, particularly through strengthening the role of the state and the judicial system in overseeing the granting of marriage dispensations. Keywords: Wali Mujbir, Early marriage, Islamic law, Children's rights Abstrak Artikel ini membahas kontroversi terkait peran wali mujbir dalam kasus pernikahan dini di Indonesia. Wali mujbir, sebagai wali yang memiliki otoritas menikahkan anak perempuan tanpa persetujuan mereka, menjadi topik perdebatan yang mengaitkan hukum Islam dengan hak asasi manusia, khususnya hak anak. Meskipun memiliki landasan kuat dalam teks-teks fikih klasik, penerapan wali mujbir di era modern, terutama di Indonesia, sering kali menimbulkan konflik dengan hukum nasional yang menetapkan batas usia pernikahan. Artikel ini menyoroti bagaimana wali mujbir kerap digunakan untuk melegitimasi pernikahan dini, terutama di wilayah pedesaan yang didorong oleh faktor sosial dan ekonomi, meski praktik ini memiliki dampak negatif terhadap kesehatan fisik, mental, dan sosial anak perempuan. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan untuk menganalisis data dari literatur hukum Islam, studi-studi akademik, dan laporan terkait dampak pernikahan dini. Temuan menunjukkan bahwa praktik wali mujbir dalam pernikahan dini sering kali menimbulkan masalah, termasuk penurunan akses pendidikan, peningkatan risiko kekerasan dalam rumah tangga, dan permasalahan kesehatan reproduksi. Kesimpulannya, meskipun wali mujbir memiliki dasar hukum Islam, praktiknya dalam konteks pernikahan dini harus dievaluasi dan disesuaikan dengan prinsip keadilan dan perlindungan hak-hak anak perempuan, khususnya melalui penguatan peran negara dan sistem peradilan dalam mengawasi pemberian dispensasi pernikahan. Kata kunci : Wali Mujbir, Pernikahan dini, Hukum Islam, Hak anak